Adolescent TV Use - Donna Davis (EDIS)
“More than likely you’ve commonly heard the most recent generations referred to as Generation X and now Generation Y. However, in a new report from the Kaiser Family Foundation, researchers renamed this younger group as 'Generation M' to stand for media influence in their lives. Indeed, there are days that I wonder if my children can unplug from the many digital and electronic devices in their lives.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.